Seeking an interoperability of disaster resilience and transformative adaptation in humanitarian design. Issue 2 (9th April 2018) - Keenan, Jesse M.
Abstract : Purpose: This paper aims to explore the conceptual, tactical and institutional tensions between short-term and long-term engagement of humanitarian actors in the built environment, as framed through disaster resilience and transformative adaptation, respectively. The paper seeks to synthesize a more resolute understanding of the limits and challenges associated with each concept in the advancement of analytical and practical clarity. Design/methodology/approach: This commentary paper is based, in part, on a literature review in disaster resilience, humanitarian design and planning and climate change adaptation scholarship. Findings: This commentary paper highlights some of the critical weaknesses associated with a disaster resilience framing of humanitarian design and planning in the built environment. Originality/value: The value of this viewpoint paper is to challenge the short-term, single equilibrium applications of disaster resilience in favor of longer-term perspectives associated with transformative adaptation. The intent is not to highlight a conceptual inferiority but to position these concepts as point and counter-point with the potential for complimentary and conflicting applications.